Augmented acetylcholine-induced translocation of RhoA in bronchial smooth muscle from antigen-induced airway hyperresponsive rats - Chiba, Yoshihiko (2001)
1. Acetylcholine (ACh)-induced translocation of RhoA in bronchial smooth muscle of repeatedly antigen-challenged rats that have a marked airway hyperresponsiveness (AHR) was examined. 2. ACh induced time- and concentration-dependent translocation of RhoA to the plasma membrane, indicating an activation of RhoA in bronchial smooth muscle. 3. The level of ACh-induced RhoA translocation was further increased markedly in the AHR group as compared to that in the control group. 4. It is suggested that the augmented activation of RhoA observed in the hyperresponsive bronchial smooth muscle might be responsible for the enhanced ACh-induced Ca(2+) sensitization of bronchial smooth muscle contraction associated with AHR.